Pengaruh Part of Speech Tagging Berbasis Aturan dan Distribusi Probabilitas Maximum Entropy untuk Bahasa Jawa Krama - Pramudita, Hafiz Ridha; Utami, Ema; Amborowati, Armadyah (Jurnal Buana Informatika, 2016)
Abstract. Javanese language is one of the local languages in Indonesia, which is used by most of the population of Indonesia. The language has complex grammar to embrace the values of decency that is determined by the use of words containing courtesy known as Raos Alus. Every word in the Javanese belongs to a certain part of speech like what happens to other languages. Part of Speech (POS) tagging is a process to set syntactic category in a word such as nouns, verbs, or adjectives to every word in the document or text. This study examined the POS Tagging with Maximum Entropy and Rule Based for Javanese Krama—Higher Javanese--by using the Open NLP library to measure the maximum entropy. The results obtained are Maximum Entropy and Rule Based can be used for POS Tagging on Javanese Krama with the highest accuracy of 97.67%.Keywords: POS Tagging, NLP, Maximum Entropy, Rule Based, Javanese KramaLanguageAbstrak. Bahasa Jawa merupakan salah satu bahasa daerah di Indonesia yang dipakai oleh sebagian besar penduduk Indonesia. Bahasa Jawa memiliki tata bahasa yang kompleks karena menganut nilai-nilai kesopanan yang ditentukan berdasarkan penggunaan dengan kata-kata yang mengandung raos alus (rasa sopan). Setiap kata dalam Bahasa Jawa memiliki jenis kata atau part of speech tertentu seperti halnya dengan bahasa-bahasa lain. POS tagging merupakah bagian penting dari cakupan bidang ilmu Natural Languange Processing (NLP). Penelitian ini menguji POS Tagging dengan Berbasis Aturan dan distribusi probabilitas Maximum Entropy pada Bahasa Jawa Krama menggunakan library OpenNLP untuk mengukur maximum entropy. Hasil yang diperoleh adalah Maximum Entropy dan Rule Based dapat digunakan untuk POS Tagging pada Bahasa Jawa Krama dengan akurasi tertinggi 97,67%.Kata Kunci: POS Tagging, NLP, Maximum Entropy, Rule Based, Bahasa Jawa Krama